(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Voice over Internet Protocol (VoIP) is a technology that enables one to make and receive calls through the Internet instead of using the traditional analog PSTN (Public Switched Telephone Network) lines. Although, VoIP is widely used technology but VoIP calls may also bring security problems such as cyber crime issues. To solve the security problems the contents of a VoIPsession should be encrypted. Thispaper focuseson authenticationissues anduser ID detection as Security is an essential part of human life depending on the voice signature of the incoming VoIP calls. Our approach defines the speech communication over the internet by detecting adversary to avoid eavesdropping. HMM )Hidden Markov Model( is used to recognize the speaker on the basis of extracted features. For this it first train the voice sample into wave file. And then, to detect the speakers of encrypted speech communications, we are proposing a new way of traffic attacks using RTP (Realtime Transport Protocol). The proposed traffic attacksarebasedonpackettiming informationonly. Thispaper shows that the proposed traffic analysis attacks can detect speakers of encrypted speech communications with high detection rates based on speech communication traces. While transmitting voice over network naive tracing technique support for alternate network to increase sanitization.